(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: Describe the epidemiological, clinical, and paraclinical characteristics, treatment results of patients with acute poisoning cases admitted to emergency of poisoning deparment of Thai Binh Pediatric Hospital from 01/01/2020 to 31/08/2021. Methods: Retrospective, prospective, descriptive case series. Results: Studying 130 patients with acute poisoning hospitalized: 65.4% of children in the 1-5 year old group, 16.2% of children over 10 years old. 94.6% of children were poisoned through the gastrointestinal tract. 80% of children poisoning by unintentional, 4.6% by suicide. The most toxic agents are chemicals, accounting for 54.6% of which are essential oils, gasoline, and kerosene. Drug poisoning accounted for 28.5% of which mainly tranquilizer poisoning. 65.4% of children hospitalized before 6 hours accounted for. Digestive and neurological symptoms account for a high percentage. Laboratory changes are mainly electrolyte disturbances. Treatment methods are mostly non-specific, accounting for 96.1%. Treatment results 97.7% of patients recovered completely, 2.3% transferred to hospital, no cases died. Conclusions: The study points out epidemiological factors, toxic agents, clinical and subclinical characteristics and appropriate treatment methods to help support treatment and prognosis for patients.